PERANCANGAN PROTOTIPE SISTEM INFORMASI PENJADWALAN MATA KULIAH PROGRAM STUDI TEKNIK INDUSTRI UNIVERSITAS UDAYANA MENGGUNAKAN FIVE PLANES METHOD - I Putu Raditya Arsadera (PT. Hasba Edukasi Mandiri, 2025)
The rise of digitalization has driven the need for efficient information systems, including course scheduling in universities, which is still largely performed manually such as in the Industrial Engineering Program at Udayana University. This manual scheduling process leads to various problems, such as schedule conflicts, misallocation of lecturers or rooms, and a heavy workload for operators. This study aims to design a course scheduling information system prototype that is both efficient and user-centered. The design process follows the Five Planes Method (strategy, scope, structure, skeleton, surface) and results in a high-fidelity prototype developed using Figma. The prototype includes features such as login, dashboard, data management, class management, automatically generated schedules with manual editing flexibility, and functions for submission, approval, and schedule download. The evaluation was conducted using Think Aloud, the System Usability Scale (SUS), and the User Experience Questionnaire (UEQ), involving five participants: two scheduling team lecturers, one head of the study program, one scheduling admin staff, and one additional lecturer. The results show a SUS score of 74 (acceptable category) and UEQ scores above 1.75 on all scales, indicating a positive user experience. The think aloud evaluation also identified areas for improvement, such as the schedule table display and the availability settings for lecturers and rooms. Overall, the prototype is considered capable of improving the efficiency and accuracy of the scheduling process, although some aspects still require refinement.